DIFFERENCES IN SOME ANTHROPOMETRIC PARAMETERS BETWEEN BASKETBALL, HANDBALL AND VOLLEYBALL ELITE ATHLETES IN KOSOVO - F. MIFTARI; M. SELIMI; H. SALIHU (Editura Universitatii Transilvania din Brasov, 2018)
The anthropometry, composition and the body structure of the elite players of ball sports played by hand, were different based on the type of sport, selection criteria, hours of practice and the specific physiological demands during the game can explain the noticed differences. Surely, much more data is required to define the anthropometric profiles of international female athletes in the sports of basketball, volleyball and handball (Bayios,et al., 2006). Summary of this study: The results showed the anthropometric measures of the professional players of the main three sports differ from one another while in the meantime there was no significant differences between the sports in the measures of  the biceps and suprailliac skinfold. Based on this study, sports have specific demands of anthropometric attritbutes which are specific for each player of the three sports: basketball,volleyball and handball. Therefore, due to the diversity of the results, coaches have to create training programmes based on the sports specific demands and all the athletes in the field.